Kinerja Guru PAI dalam Meningkatkan Mutu Pendidikan Melalui RPP Kurikulum 2013 Di SMP Islam Azizi Medan - Cici Rusmaida; Neliwati; , Priska; Safira Nur Permana (Mu'allim, 2023)
Teachers with expertise in their field are required to intervene in order to enhance the quality of Islamic Religious Education. Because teachers play a crucial role in education, it is necessary to focus more on training qualified teachers so that they can assist students in learning. The teacher plays a crucial role in determining the quality of his or her instruction. Teacher performance, as demonstrated by their performance in class, must support the implementation of the Learning Implementation Plan (RPP). The primary responsibility of the teacher is to effectively implement the teaching and learning process in the classroom. The motivation behind this study was to decide the exhibition of PAI educators in working on the nature of picking up, including: ( 1) capability; 2) self-control; and, thirdly, the challenges it faces. This study employs descriptive and qualitative methods. The following methods were used to collect data: observation and interviews PAI teachers at Medan's Azizi Islamic Private Middle School served as the study's subjects.